2019
DOI: 10.1016/j.jamda.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein Intake and Falls in Older People: Longitudinal Analyses From the Osteoarthritis Initiative

Abstract: Objectives: Literature regarding dietary protein intake and risk of falls is limited to a few studies with relatively small sample sizes and short follow-ups, which have reported contrasting findings. Thus, we investigated whether dietary protein intake is associated with risk of falls in a large cohort of North American adults. Design: Data were drawn from the Osteoarthritis Initiative, a cohort study, with 8 years of follow-up. Setting and participants: Community-dwelling adults with knee osteoarthritis or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…However, Nicola et al. found high dietary protein intake could increase the risk of falls in older persons [45 , 46] . These findings show that the role of protein intake in arthritis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, Nicola et al. found high dietary protein intake could increase the risk of falls in older persons [45 , 46] . These findings show that the role of protein intake in arthritis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one study of 1429 Australian women aged ≥70 years, it was found that those with higher total and cruciferous vegetable intake had lower risk for injurious falls (5). Furthermore, in a study of 4450 North America adults (mean age 61.2 years, females = 59.6%), it was found that high dietary protein intake may increase the risk of falls in older people (6). Other studies have identified an association between micronutrient deficiencies and a higher fall risk including for example Vitamin D (7) and Vitamin B12 (8).…”
Section: Introductionmentioning
confidence: 99%